Sistem Pewarisan Tari Zapin Penyengat di Pulau Penyengat Inderasakti Kepulauan Riau - Melany, Sandra; Mansyur, Herlinda (Lembaga Yasin AlSys, 2023)
This research aims to determine the inheritance system of the Zapin Penyengat dance in a closed and open manner on Penyengat Inderasakti Island, Riau Island. Inheritance activity is an activity of transferring, continuing, inter-generational ownership to maintain dance and maintain cultural values in the past so that there are always. This type of research is qualitative with descriptive analysis method. The research object of the Zapin Penyengat dance,with the main instrument of this research being the researchers themselves by making direct observations in the field with supporting instruments such as; statioery, digital cameras, and tape recprders. The results of this research show that the inheritance system in the Zapin Penyengat dance in Penyengat Inderasakti, Riau Islands experienced two inheritance systems, namely the closed inheritance system from 1919 to 2009 and the open system from 2009 to the present. This dance was created during the late Riau-Lingga Malay kingdom on Penyengat Inderasakti Island, Riau Archipelago with a closed system by Mr. Muhammad Ripin in 1919, passed on to King Ahmad bin Raja Daud in 1919, then passed on to King Ahmad bin Raja Daud in 1919 King Mahmud bin Raja Ahmad in 1919. 1950, and inherited it to King Nafisah bin Raja Ahmad in 1970 and Tohar Fahlevy in 2009. In 2009 Tohar Fahlevy banned Ihsan, Riyan and Rizki as the first towing with an open system